Antecedents of Organizational Slack - Sharfman, Mark P.; Wolf, Gerrit; Chase, Richard B.; Tansik, David A. (Academy of Management Review, 1988)
Organizational slack has been widely discussed, but only in its role as an antecedent of performance, political behavior, bankruptcy, and other phenomena. A model that describes the antecedents of organizational slack is presented here. It contains three sets of predictors: environmental contingencies, organizational characteristics, and the values and beliefs of dominant coalition. Hypotheses detailing how each set of predictors leads to the development of different levels and types of slack resources are presented.